The Role of Proteasomes in the Thymus - Frantzeskakis, Melina; Takahama, Yousuke; Ohigashi, Izumi (Frontiers in Immunology, 2021)
The thymus provides a microenvironment that supports the generation and selection of T cells. Cortical thymic epithelial cells (cTECs) and medullary thymic epithelial cells (mTECs) are essential components of the thymic microenvironment and present MHC-associated self-antigens to developing thymocytes for the generation of immunocompetent and self-tolerant T cells. Proteasomes are multicomponent protease complexes that degrade ubiquitinated proteins and produce peptides that are destined to be associated with MHC class I molecules. cTECs specifically express thymoproteasomes which are essential for optimal positive selection of CD8+ T cells, whereas mTECs, which contribute to the establishment of self-tolerance in T cells, express immunoproteasomes. Immunoproteasomes are also detectable in dendritic cells and developing thymocytes, additionally contributing to T cell development in the thymus. In this review, we would like to summarize the functions of proteasomes expressed in the thymus, focusing on recent findings pertaining to the thymoproteasomes and immunoproteasomes.